Primary torsion of the omentum mimicking acute appendicitis: Report of a case - (:unkn) unknown (My University, 1997)
A case of primary omental torsion seen in a 26-year-old man is discussed. All signs and symptoms mimicked acute apendicitis. The patient underwent emergency laparotomy in which a normal appendix and serohemorrhagic fluid in the pelvis were observed. The pathological diagnosis was a primary torsioned omentum which was thus excised. This case helps to emphasize the importance of a routine exploration of the abdomen when serohemorrhagic fluid is found at the time of laparotomy in the absence of any pathological condition in the pelvis.
Keywords: omental torsion